L’assurance et la réassurance – un monde de problèmes (Assurances, 1984)
Every year, insurers, reinsurers and a large number of reinsurance brokers meet in Monte Carlo at the beginning of September. The meeting has become known as the Rendez-Vous de Septembre. Very little business is done, but there is the opportunity for a large number of insurance people to get together and discuss their particular problems. A certain number of speeches are given, and we give the full text of one, that of Mr. James J. Meenaghan. As for Lloyd's, we include excerpts from the text presented by Mr. B.L. Brennan, Deputy Chairman of Lloyd's of London.